On star-dagger matrices and the core-EP decomposition - Ferreyra, David Eduardo (2024)
The concept of star-dagger matrices was introduced in 1984 by Hartwig and Spindelböck. While they completely characterized the star-dagger matrices by using a block decomposition of the form PQ00, they also proposed the following open problem: “Can the triangular form PQ0Rbe used to obtain further results on the star-dagger matrices?” In this paper, we have attempted this open problem by using an upper-triangularization of Schur's type for a square matrix, namely, the core-EP decomposition. Furthermore, similar problems regarding bi-dagger and bi-EP matrices are investigated.